Implementação computacional de um modelo de fissuração para o concreto baseado no método dos elementos finitos estendido (XFEM) - Kelson Pothin Wolff (2010)
This master's thesis is concerned about computational implementation of amodel able to describe concrete behavior under cracking. The concrete cracked region is represented by a constitutive relation based on Cohesive Crack Model, while the undamaged bulk keeps a linear elastic response. These constitutive relations are integrated with eXtended Finite Element Method as sumptions to form a model that introduces a jump in displacements field of a standard finite element. Thus, a discrete crack propagation is simulated due a discontinuity that is induced instandard finite element approximation fields. The propagation criterium is based on tensile strength material parameter and the crack geometry is defined by a set of linear segments. In this way, the conceived model allows freely crack propagation over the standard mesh, even at the element's interface. The model was implemented in numerical nucleus of computational system INSANE (INteractive Structural ANalysis Environment), enabling the simulation of crack propagation problems involving concrete specimens under modes I, II and mixed mode loadings. The results are found within expected response range. The main drawback found is related to the chosenpropagation criterium that is not reliable in predicting the correct direction of crack when the analysis reaches high stresses levels.